2013
DOI: 10.1002/ptr.5009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Blackcurrant Products on Gut Microbiota and on Markers of Risk for Colon Cancer in Humans

Abstract: The purpose of this study was to determine in healthy humans whether First Leaf (FL; composed of blackcurrant extract powder, lactoferrin and lutein) and Cassis Anthomix 30 (CAM30; blackcurrant extract powder) can positively modify the colonic microbiota by enhancing the growth of the beneficial bacteria and inactivating the toxic bacterial enzymes which are known to be involved in colonic carcinogenesis. Thirty healthy adult male and female volunteers were recruited for this study. Fluorescent in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 36 publications
0
56
0
1
Order By: Relevance
“…reviewed studies on the modulation of gut microbiota by dietary polyphenols according to experimental design . Food polyphenols or their extracts have been shown to increase Lactobacillus and Bifodobacteria in the majority of the animal and human intervention studies, yet some observed decreases or no change …”
Section: Discussionmentioning
confidence: 99%
“…reviewed studies on the modulation of gut microbiota by dietary polyphenols according to experimental design . Food polyphenols or their extracts have been shown to increase Lactobacillus and Bifodobacteria in the majority of the animal and human intervention studies, yet some observed decreases or no change …”
Section: Discussionmentioning
confidence: 99%
“…If retinal parainflammation develops into a chronic retinal malfunction, and constitutes a shift in the normal homeostasis or “balance” to adapt to the new physiological or metabolic conditions of AMD (as occurs in many other chronic inflammatory disease states), the disruption in the interrelationships between nutrition, the microbiome, and host metabolism may be key elements in the disruption of normal homeostasis. The gut microbiome composition may vary according to macro/micronutrient dietary habits, as shown in several studies . The redox state also strongly modulates the gut microbiota .…”
Section: Zinc and The Microbiomementioning
confidence: 97%
“…ACF can be classified according to their morphological subtypes and are identified by the (i) number of crypts (ii) crypt size and (iii) crypt multiplicity. Molan et al (2014) reported that consumption of plant antioxidants promote the growth of beneficial bacteria and lower the numbers of other bacteria. β-glucosidase contributes to the hydrolysis of glucose monomers from nonstarch polysaccharides, however, it is also possible for β-glucosidase to be involved in the formation of toxic aglycons from plant glucosides (Pool-Zobel et al, 2002).…”
Section: Introductionmentioning
confidence: 98%